PENGARUH FEE AUDIT, AUDIT TENURE, ROTASI AUDIT DAN REPUTASI AUDITOR TERHADAP KUALITAS AUDIT - Listiya Ike Purnomo; Jihan Aulia (Universitas Pamulang, 2019)
This study aims to empirically examine the effect of audit fees on audit quality, the effect of audit tenure on audit quality, the effect of audit rotation on audit quality, and the effect of auditor reputation on audit quality. The population of this study is property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. The research sampling technique used purposive sampling. The research samples obtained were as many as 25 property and real estate companies in 2013-2017. The analytical method used is logistic regression analysis. The results based on partial hypothesis testing indicate that audit fees affect audit quality and audit tenure affect audit quality. While audit rotation does not affect audit quality and auditor reputation does not affect audit quality. Keywords: Audit Quality, Audit Fee, Audit Tenure, Audit Rotation and Auditor Reputation